Prevalence and associated factors of Treponema pallidum infection in a rural area of southwestern China - Shi, Ying; Yang, Ya; Wang, Yingjian; Yang, Dongjian; Yang, Yu; Dong, Shurong; Li, Chunlin; Chen, Yue; Jiang, Qingwu; Zhou, Yibiao (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Epidemiological data on Treponema pallidum infection are scarce from the southwestern region of China. The purpose of this study was to determine the distribution and determinants of T. pallidum infection in the region. Methods A community-based cross-sectional study of 2608 participants aged ≥14 years was conducted in a rural area of southwestern China in 2014–15. A pretested questionnaire was used to collect sociodemographic characteristics and other factors associated with T. pallidum infection. The diagnoses of T. pallidum, human immunodeficiency virus (HIV), hepatitis B virus (HBV) and hepatitis C virus (HCV) infections were determined by commercial test kits. Logistic regression analysis was used to determine the correlates for T. pallidum infection, and adjusted odds ratios (aORs) and 95% confidence intervals (CIs) were calculated. Results The prevalence of T. pallidum infection was 1.2% (95% CI 0.8 to 1.7%). Risk factors varied by gender. In the male group, T. pallidum infection was significantly associated with ever injection drug use (aOR = 9.42, 95% CI 2.47 to 35.87) and HCV infection (aOR = 13.28, 95% CI 3.20 to 51.70). In the female group, correlates for T. pallidum infection included spouse having syphilis (aOR = 126.66, 95% CI 7.58 to 2122.94), ever having blood transfusion (aOR = 10.51, 95% CI 1.58 to 41.21) and HBV infection (aOR = 4.19, 95% CI 1.35 to 10.93). Conclusions The prevalence of T. pallidum infection was high in the rural area of southwestern China. Correlates for T. pallidum infection varied with sex specific. Intervention should be developed for the prevention and control of T. pallidum infection.